MENGEMBANGKAN TOLERANSI DALAM UPAYA MEMBANGUN MODERASI BERAGAMA DI INDONESIA (Telaah terhadap gagasan moderasi beragama dalam buku Moderasi Beragama terbitan Kementerian Agama RI) - Dadi, Kanisius Komsiah; Wowiling, Katarina Vonny (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
The reality of the Indonesian nation as a pluralistic nation is a positive thing. However, in the reality of the dynamics of today's society, the positive value of plurality is harmed by conflicts between adherents of religion, ethnicity, race, and class. In responding to this situation, the younger generation, especially elementary school-aged children in grade VI or early teens as part of the community, need to be educated from an early age so that they have an attitude of tolerance, openness, mutual respect, and respect for diversity in society or called religious moderation. The idea of religious moderation is understanding religious differences and not being extreme in religion. The purpose of writing this thesis is to find and analyze the ideas of religious moderation from the main sourcebooks and other sources; apply the principles of religious moderation, especially tolerance, in the lives of Indonesia's young generation. This research method is the literature review. The main book studied is the Religious Moderation book written by the Ministry of Religious Affairs. The findings or results of the author's research show that one of the basics in religious moderation is active tolerance.